Acquired Tracheoesophageal Fistula in Infancy and Childhood - Osama A. Bawazir (Journal of King Abdulaziz University: Medical Sciences, 2023)
Acquired tracheoesophageal fi stula in infancy and childhood is a very rare condition with no epidemiological data available in the literature for it. There is a huge similarity of the condition to the congenital acquired tracheoesophageal fi stula. Management of children with this condition can be diffi cult with a high risk of complication. To provide a successful management of the condition, there are some points that need to be addressed about acquired tracheoesophageal fi stula. In this report, the author presents fourteen different cases of acquired TEF with diff erent etiologies over 11 years (2006 - January 2017) who were referred for management to tertiary care hospital in Jeddah, KSA; all patients had removal of the foreign body followed by surgical repair of the fi stula. This report describes the detailed steps of our surgical repair, including the approach to the fi stula and the type of repair pointing out the importance of removal of the scar tissue and use of interposition vascular grafts with suture lines separation. This study presents our experience in management and surgical repair of the acquired tracheoesophageal fistula.